The Changing Role of University Faculty in the Era of Artificial Intelligence: A Systematic Literature Review - Sulisworo, Dwi; Ofluoglu, Gokhan (Buletin Edukasi Indonesia, 2025)
The integration of Artificial Intelligence (AI) in higher education has profoundly influenced teaching and learning processes. This study investigates the evolving roles of university faculty in the AI era by synthesizing findings from peer-reviewed literature, policy reports, and institutional research. A systematic literature review was conducted based on 32 key sources published between 2018 and 2024. The results reveal three significant transformations: (1) pedagogical innovations with AI-assisted tools, (2) the shift in administrative responsibilities and decision-making supported by AI analytics, and (3) emerging ethical roles and the need for AI literacy among faculty. The study concludes that AI enhances efficiency and demands a reconfiguration of professional identity, calling for continuous professional development, ethical frameworks, and institutional support.